Exploring Electron Transporting Layer in Combination with a Polyelectrolyte for n‐i‐p Perovskite Solar Cells. Issue 17 (8th July 2020) - Sun, Mengjie; Zhang, Huimin; Liang, Chunjun; Ji, Chao; Jing, Xiping; Sun, Fulin; Song, Qi; You, Fangtian; He, Zhiqun
Abstract: A double‐layered poly(ethylenimine) ethoxylated (PEIE)/SnO2 composite structure, the ultrathin PEIE in contact with an indium‐tin‐oxide electrode, and an SnO2 layer interfaced with the perovskite, is developed as an electron‐transport layer (ETL) in the preparation of perovskite solar cells. The surface energy and the work function of the top SnO2 side of the composite ETL can be finely adjusted by tuning the underneath polyelectrolyte PEIE layer. These control the nucleation process in the crystallization of the perovskite layer and reduce the energy level mismatch between the electron transport and perovskite layers. High performance perovskite solar cells having a certified power conversion efficiency of 21.3%, with negligible hysteresis are achieved. Abstract : An ultrathin polyelectrolyte PEIE is Inserted underneath of SnO2 layer to form a double‐layered PEIE/SnO2 electron transport composite. Work function and surface energy of the SnO2 top surface is lowered. This reduces energy level mismatch at the interface for a better electron transport and induces large grain sizes in perovskite layers. Photovoltaic performance of the device is substantially improved.